Estimating Targeted Group Threats in the Juvenile Justice System: An Examination of Disproportionate Minority Contact at Preadjudication Detention - Zane, Steven N. (Crime & delinquency, 2024)
This study examines whether group threats in the surrounding social context positively moderate disproportionate minority contact at preadjudication detention in the juvenile justice system. To do so, the study utilizes a multijurisdictional sample of 96,619 juvenile court referrals across 139 counties (within four states) to examine a series of group threats?racial, ethnic, economic, and age threat. Due to the nested structure of the data, multilevel models are employed. To test the hypotheses, cross-level interactions between group threats and defendant race and ethnicity are estimated following current best practices for measuring interactions with nonlinear dependent variables. Findings indicate mixed and mostly limited support for the group threat hypotheses, consistent with prior mixed findings. Implications for research and policy are discussed.